Assisted Versus Unassisted Domiciliary Alcohol Detoxification: A Randomized Controlled Trial - Sneha B. Suresh; Anil V. Rane (Indian Journal of Psychological Medicine)
Background: Detoxification stands as a crucial phase in the treatment of alcohol use disorders (AUD), yet only limited data is available on the outcomes of home-based detoxification. Assisted domiciliary detoxification involves monitoring an individual’s withdrawal progress, while offering psychosocial support and detoxification services in the comfort of their home. To study outcomes of assisted over routine domiciliary alcohol detoxification in randomized controlled trials. Methods: 100 consenting male patients who were advised of domiciliary detoxification were randomized into intervention ( n = 49) and control ( n = 51) groups. A predesigned semi-structured questionnaire was used to assess the socio-demographic and drinking-related variables. Both groups received routine care for alcohol withdrawal from respective treating doctors. Additionally, the intervention group received two sessions of brief intervention for alcohol and daily phone call assistance. Records were kept for adverse events. Phone calls were discontinued once detoxification was completed. Outcomes were measured for successful completion of detoxification and abstention from alcohol at the end of one month. Results: The intervention group had significantly higher successful detoxification rates (85.7% vs. 62.7%, p = .008) and significantly higher abstinence days at the end of one month compared to the control group (22 vs. 10 days, p < .001) with an effect size of 1.2 (confidence interval (CI) 0.69–1.53). Conclusion: This study demonstrates that receiving assistance in the acute phase of domiciliary detoxification helps in a successful detoxification and achieving a significant level of abstinence at the end of one month compared to the control group.